2021
DOI: 10.1038/s41563-021-01114-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional atomic packing in amorphous solids with liquid-like structure

Abstract: Liquids and solids are two fundamental states of matter. However, due to the lack of direct experimental determination, our understanding of the 3D atomic structure of liquids and amorphous solids remained speculative. Here we advance atomic electron tomography to determine for the first time the 3D atomic positions in monatomic amorphous materials, including a Ta thin film and two Pd nanoparticles. We observe that pentagonal bipyramids are the most abundant atomic motifs in these amorphous materials. Instead … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 70 publications
(105 reference statements)
0
53
0
Order By: Relevance
“…To address these critical issues of core-shell interfacial structure, here we synthesized polycrystalline pentagonal bipyramid and monocrystalline truncated octahedron palladium-platinum CS-NPs using two-step chemical reduction, and then probed the 3D atomic structures of CS-NPs at the single-atom level. The 3D atomic coordinates and chemical composition of Pd@Pt CS-NPs with different morphology and size were determined using atomic resolution electron tomography (AET), which has been a powerful tool for atomic-scale structural characterization in 3D and even 4D 19,[26][27][28][29] . We discovered a 3D atomically diffuse core-shell interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these critical issues of core-shell interfacial structure, here we synthesized polycrystalline pentagonal bipyramid and monocrystalline truncated octahedron palladium-platinum CS-NPs using two-step chemical reduction, and then probed the 3D atomic structures of CS-NPs at the single-atom level. The 3D atomic coordinates and chemical composition of Pd@Pt CS-NPs with different morphology and size were determined using atomic resolution electron tomography (AET), which has been a powerful tool for atomic-scale structural characterization in 3D and even 4D 19,[26][27][28][29] . We discovered a 3D atomically diffuse core-shell interface.…”
Section: Introductionmentioning
confidence: 99%
“…The final classification results are shown in Supplementary Table2.The structure of two five-fold twinned nanoparticles is analyzed by two methods, i.e., local bond orientational order (BOO) parameters and polyhedral template matching33 . Averaged local BOO parameters ( 4 and 6 ) and normalized BOO parameter for ideal face-centered cubic (fcc) structure are calculated based on the procedure published elsewhere29 , using the first-nearest-neighbor shell distance(3.35 Å) as a constraint. By applying polyhedral template matching , PB/EPB particle was separated into five fcc grain and a five-fold coaxial twin boundary which locally possessing hexagonally close-packed environment.…”
mentioning
confidence: 99%
“…Non-crystalline materials, such as amorphous metals, alloys, and glasses, are employed in a wide range of industrial processes and applications. , The atomic arrangement of disordered systems determines their physical, mechanical, chemical, and electrical properties. Several studies showed a strong correlation between the configurational local order and the electronic, , magnetic, catalytic, and corrosion-resistance properties of disordered systems, as found, for example, for the high-entropy alloys. , The structural order in amorphous solids is difficult to characterize, and it is far from being understood . Despite the lack of translational periodicity, amorphous systems are not completely random, being organized in hierarchical local structures at different length scales. The presence of microscopic-ordered arrangement, repetitive units, or defects is responsible for the macroscopic properties of the whole material.…”
Section: Introductionmentioning
confidence: 99%
“…The authors were able to parse out the interconnected geometries of the polyhedra, finding that face-sharing is common in densely packed clusters. More recently, Voronoi analysis was combined with atomic electron tomography and ePDF for the study of monatomic amorphous Ta and Pd materials . The authors demonstrated that experimental PDFs of amorphous regions were consistent with a MD-generated PDF of Ta liquid, indicating that the packings of atoms in these two phases closely resemble each other.…”
Section: Applications To Disordered Materials Systemsmentioning
confidence: 94%